Masalah dan Solusi Alternatif Pembelajaran Perancangan Elemen Mesin - Edi Septe; Niswardi Jalinus (invotek, 2019)
The purpose of this article is to identify problems and alternative solutions in design of machine elements learning, in order to be used as a guide to development of learning model in the future. This literature review is conducted through searching journal within the scope of machine design learning with google scholar, www.springer.com, www.elsevier.com, www.sagepub.com and international conference proceedings resources. By searching keywords: machine design, machine design learning, teaching and learning of machine design, mechanical design, machine elements, obtained 100 journals and related proceedings, which selected into 79 journals and proceedings that describe the problems and alternative solutions according to the topic of this article. The results of the study shown the main problems in design of machine elements learning is: the learning still apply the traditional method, the sudject materials is not relevant to the field needs, the students do not have sufficient initial knowledge and experience, the lecturers lack experience guiding students to practice, lack of student English skills, the lack of practical exposure of students, and no validated framework for designing instructional development in changing traditional models of instructional design. Furthermore the alternative solutions offered are: make students learn actively and advance the concrete working mode, the course material is directed to design complex system through project engineering program, develop the model of 'joint experiment' study which discuss field problem, design activities done in the laboratory to apply classroom learning into a real world or apply the virtual laboratory modules or interactive laboratory simulations, and learning is done with a team-based hands-on approach, which provides students with practical experience in designing, fabricating and testing the strength and efficient mechanical systems.